WHAT DO INDONESIAN NETIZENS THINK ABOUT THE EMONEY? : A SENTIMENT ANALYSIS WITH MACHINE LEARNING - Timur, Yan Putra; Ratnasari, Ririn Tri; Hadi, T.Saipul; Sari, Dyah Permata (Universitas Airlangga, 2023)
This study aims to identify the most popular topics and words in conversations in cyberspace with the issue of E-Money. In addition, the research aims to find out how netizens feel about E-Money with the help of Machine Learning. This study uses a quantitative method with a sentiment analysis approach using the Machine Learning program, namely Orange Data Mining. The data used are tweets originating from Twitter that were crawled from April 5, 2023, to April 12, 2023. Researchers used the keywords E-Money,